Cost-effectiveness of home-based stroke rehabilitation across Europe: A modelling study - Candio, P; Violato, M; Luengo-Fernandez, R; Leal, J (Elsevier, 2022)
The aim of this study was to explore the cost-effectiveness of home-based versus centre-based rehabilitation in stroke patients across Europe. A state-transition cohort model was developed to simulate the impact of the intervention in 32 European countries. A cost-utility analysis was conducted from a societal perspective including healthcare, social care and informal care costs, and productivity losses. Health outcomes were expressed as QALYs. Sensitivity analyses were conducted concerning model input values and structural assumptions. Data were obtained from a population-based cohort and previously published studies. Across Europe, over 855,000 patients with stroke would be eligible for rehabilitation in 2017. Europe-wide implementation of home-based rehabilitation was estimated to produce 61,888 additional QALYs (95% CI: 3,609 to 118,679) and cost savings of €237 million (95% CI: -237 to 1,764) and of €352 million (95% CI: -340 to 2,237) in health- and social-care and societal costs, respectively. Under base case assumptions, home-based rehabilitation was found highly likely to be cost-effective (>90%), compared to centre-based rehabilitation, in most European countries (29 out of 32). Evidence from this study suggests that a shift from a centre-based to a home-based approach to stroke rehabilitation is likely to be good value for money in most European countries. Further research should be conducted to assess the generalisability of these findings to local settings.